1978
DOI: 10.1161/01.cir.57.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The role of the exercise test in the evaluation of patients for ischemic heart disease.

Abstract: A cohort of 1472 patients who underwent both exercise stress testing and coronary angiography within six weeks was examined. The data indicated that a combination of exercise parameters is both diagnostically and prognostically important. Almost all patients (greater than 97%) who had positive exercise tests at Stage I or Stage II had significant coronary artery disease. More than half of these (greater than 60%) had three vessel disease and over 25% had significant narrowing (greater than 50%) of the left mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
99
0
5

Year Published

1979
1979
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 466 publications
(111 citation statements)
references
References 15 publications
7
99
0
5
Order By: Relevance
“…of three vessel disease and 3 lI~ of left main disease among patients with negative exercise tests referred for the evaluation of possible coronary heart disease (13). The percentage of false negative tests in these series is 40o/c (present study) 35 'Ii (10), and 43",( (13). These data indicate that the negative exercise test has little value in excluding coronary heart disease in symptomatic patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…of three vessel disease and 3 lI~ of left main disease among patients with negative exercise tests referred for the evaluation of possible coronary heart disease (13). The percentage of false negative tests in these series is 40o/c (present study) 35 'Ii (10), and 43",( (13). These data indicate that the negative exercise test has little value in excluding coronary heart disease in symptomatic patients.…”
Section: Discussionmentioning
confidence: 51%
“…McNeer et al have reported a prevalence of 14 lie. of three vessel disease and 3 lI~ of left main disease among patients with negative exercise tests referred for the evaluation of possible coronary heart disease (13). The percentage of false negative tests in these series is 40o/c (present study) 35 'Ii (10), and 43",( (13).…”
Section: Discussionmentioning
confidence: 55%
“…15 Despite the good agreement between exercise tests and clinical follow-up, the correlation between exercise electrocardiography and coronary angiography has been poor. 3,16 Indeed, ST-segment depression as assessed by electrocardiography represents a relatively insensitive marker of myocardial ischemia. 1,2 Several studies have shown a poor relation between the heart rate at the point of induction of WMA and at the onset of significant ST-segment depression during stress Figure 3 Receiver-operator characteristic curves for diagnostic accuracy of percent diameter stenosis and minimal lumen diameter for occurrence of exercise-induced wall motion abnormality on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Consequently, the relation between the ischemic threshold assessed by electrocardiographic changes during exercise and coronary arteriography has been poorer than expected. 3 Exercise echocardiography (EE) is an accepted tool for the assessment of the functional significance of coronary obstructions among patients with coronary artery disease (CAD).…”
mentioning
confidence: 99%
See 1 more Smart Citation